The Information System for Improving the Effectiveness of ECE Services During the COVID-19 Pandemic - Subhan, Subhan (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2022)
Purpose – The pandemic-era policy that requires schools to conduct face-to-face meetings is an issue that cannot be taken